Evaluation of Intracochlear Pressure and Fluid Distribution in 3D-Printed Artificial Cochlear Models and Human Petrous Bones - Rayoung Kim; Matthias Schürmann; Lars-Uwe Scholtz; Ingo Todt (Brain Sciences)
Introduction: The important factor in applying substances for inner ear therapy is the atraumatic execution, as well as effective concentration uniformly distributed in all regions of the cochlea within a reasonable time frame. This study investigates whether an additional cochlear opening (“second-hole technique”) can improve fluid distribution and reduce intracochlear pressure during dye delivery into the cochlear models and human petrous bone. Material and Methods: Three experimental setups were used: an uncoiled scala tympani model, a full-scale 3D-printed cochlear model, and a human petrous bone. In all cases, 1% methylene blue-stained saline was infused using a cochlear catheter (MED-EL, Innsbruck, Austria) through the round window. Intracochlear pressure was measured via fiberoptic pressure sensors inserted through a burr hole (artificial cochlear models) or at the lateral semicircular canal (human petrous bone). A second hole was made on the helicotrema in the inner ear models or at the oval window of the human petrous bone to examine the effect of a second hole on intracochlear pressure and fluid distribution. Dye distribution and intracochlear pressure were measured in 3D artificial models at two flow rates (0.2 and 0.4 mL/h). The intracochlear pressure were measured in the human petrous bone at a fixed rate (0.4 mL/h). Results: The use of a second hole significantly improved dye distribution in 3D models at both flow rates (p < 0.05) and led to earlier saturation-level distribution. Intracochlear pressure remained significantly lower and more stable in models with a second hole (p < 0.05). In human petrous bones, pressure fluctuation was reduced by the second hole, though pressure still increased over time. Conclusions: Using a second-hole technique leads to a faster, uniform level of dye distribution throughout the cochlear models, as well as a lower intracochlear pressure, which can be assumed to be an essential factor for hearing preservation during dye application.